TJNPR 2019
DOI: 10.26538/tjnpr/v3i4.6
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicological Evaluations of the Methanol Leaf Extract of Justicia flava (Vahl) Acanthaceae in Mouse Models

Abstract: Africa 6. It is called "Afema" in local Asante-Twi language in Ghana and 'Ighereje'in Urhobo language of Nigeria. It is an abundant perennial herb also referred to as yellow Justicia of the Acanthaceae family because of its distinct yellow flowers. It is an erect plant of about 450 mm high. Toxicity profile of plants provides necessary information to guide natural product's use. This study, therefore, examines the acute toxicological profile of the leaves of J. flava using mouse models. Materials and Methods P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…This efficacy is comparable to the reduction in DNA damage and enhanced cell division in rats exposed to petroleum-tainted feed and administered with standard ascorbic acid. In fact, previous studies presented the medical ability of this plant [27]. Similarly, this observation is consistent with the papers where JFME was involved in reducing the damage caused by petroleum-tainted diet in the liver of rats [37].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This efficacy is comparable to the reduction in DNA damage and enhanced cell division in rats exposed to petroleum-tainted feed and administered with standard ascorbic acid. In fact, previous studies presented the medical ability of this plant [27]. Similarly, this observation is consistent with the papers where JFME was involved in reducing the damage caused by petroleum-tainted diet in the liver of rats [37].…”
Section: Resultssupporting
confidence: 91%
“…Moreover, various substances have been used as counter measures to crude oil toxicities. These substances include various vitamins [21,22,23,24] organic and inorganic substances [9,5,25] and various plant extracts [9,26,27]. A review of literature shows that there is one important plant with a lot of curative ability [27].…”
mentioning
confidence: 99%
“…This is a pilot study that clearly shows the tocolytic potential of JF for human uterine contractility disorders. Previous safety studies on mice showed JF to be relatively safe, even at high doses of 5 g kg −1 (Bafor et al., 2019b). Our previous studies have also shown JF to have mild oestrogenic activities at low doses (Bafor et al., 2020), which is beneficial to its continued use on humans.…”
Section: Resultsmentioning
confidence: 98%
“…One other such plant of growing interest is Justicia flava . The leaves of J. flava are regularly used in the south of Nigeria to prevent miscarriages (Bafor, Ukpebor, Omoruyi, Ochoyama, & Odega, 2019) possibly through myometrial contractility inhibition. For this reason, the plant was selected and explored extensively on mouse models for its activity on uterine contractility and the female reproductive system (Bafor et al., 2020; Bafor et al., 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Signs for toxic manifestations like abnormal motor activity, alteration in water or food intake, writhing, straub reaction, sedation, diarrhoea, piloerection, opisthotonus, exophthalmos and tremors were observed for in all groups [15].…”
Section: Observation and Examination Methodsmentioning
confidence: 94%